Inversion of the Main Trends of Digitalization in the Educational Space - D. P. Kozolupenko (Высшее образование в России)
The modern social space is increasingly determined by the trends of digitalization. Today we can talk about such consequences of digitalization as the appearance of scattered identity and distancing – a new kind of socialization in the conditions of spatial separation and overcoming social deprivation and virtual transgression. These trends manifest themselves in all spheres – cultural, economic, political, etc. But at the same time, processes of a different kind are also taking place in the field of education: processes that represent a kind of inversion of the digitalization influence on our perception of the world, self-perception and the sphere of our everyday life. The article examines three such major trends and their inversions in the educational space of our time. 1. The tendency to eliminate the intermediary in the educational space leads to an opposite effect of multiplying intermediaries and awareness of teacher’s unavoidability as one of the main participants in education, both due to the complexity and inaccessibility for direct study of educational material and the fact that education is not based on transmission (in which the intermediary could theoretically be eliminated), but creation based on the phenomenon of meeting. 2. The transgressive tendency as “going beyond” and even erasing boundaries is transformed in the educational space into a tendency of distancing as a double movement of alienation (delineation) and inclusion (communion), in which the blurring of the boundary between the public and intimate, the space of self-organization in the order of the norm and the space of spontaneity, real and virtual, etc. is accompanied by the establishment of a new type of socialization in conditions of spatial disunity and social deprivation. 3. The appearance of a diffuse identity reinforced by the tendency to glocalization in the socio-political sphere and the transition to a transmedia narrative in the cultural and entertainment sphere, in the digital space of education is transformed into the possibility of self-actualization, self-expression, turning the modern educational space into a mythopoetic “world of all kinds” and anthropological singularity.